Efficacy of surgeon performed ultrasound scan in localization of parathyroid adenomas in patients with primary hyperparathyroidism. (1st March 2022) - Habib, Ayaaz; Snowden, Chris; England, James
Abstract: Introduction: The success of minimally invasive parathyroid surgery is largely based on accurate preoperative localization of parathyroid adenomas. In the U.K, NICE guidance recommends either ultrasound scanning alone or combined with sestamibi scintigraphy to help guide surgery. In the recent past, surgeon performed ultrasound (SUS) has been adopted in North America and Australia for preoperative localization with a sensitivity of 63–91%. This was equivalent or superior to radiology performed ultrasound (RUS). In comparison, data from the U.K for surgeon performed imaging is sparse. In this study, we investigate the efficacy of surgeon performed ultrasound in localization of parathyroid disease and discuss its cost benefits. Methods: This is a prospective study with data collected from November 2019 to June 2021. All patients had primary hyperparathyroidism and underwent either MIBI, radiology performed ultrasound or both. A single experienced surgeon performed ultrasound on all patients under general anaesthesia. The intraoperative findings were used to determine the accuracy of all imaging techniques. Results: A total of 46 patients underwent surgery and were found to have single gland disease. The categories were: Double imaging (n=17), MIBI (n=34), RUS (n=22), SUS(n=46), no imaging (n=9). MIBI, radiology performed ultrasound and surgeon performed ultrasound had sensitivities of 58%, 55% and 81% respectively. 8 patients had ectopic glands and were not included in the sensitivity analysis of ultrasound scans. Conclusion: Surgeon performed ultrasound by an experienced provider is effective in localizing parathyroid adenomas and guides minimally invasive surgery. It could significantly reduce costs associated with outpatient radiology performed ultrasound scanning